TINJAUAN YURIDIS KONVENSI JENEWA IV TAHUN 1949 TERHADAP NEGARA-NEGARA YANG BERPERANG MENURUT HUKUM INTERNASIONAL - Rafika Mayasari Siregar; Abdul Rahman; Arif Arif (Journal of USU International Law, 2013)
ABSTRACT Rafika Mayasari Siregar[1] Abdul Rahman[2] Arif[3] Wars arise because of the hostility between the two countries (narion, religion, ethnic group, and so on) and the great battle armed between two or more forces. Of the two countries were at war and in war and the armed conflict civilians always be a victim. Wars happens between the two countries were at war causing civilians suffered minor injuries, serious injuries, and even death. I lay out the problems that are how the protection of civilians during war according to the Geneva Convention IV of 1949, how the role of International Committee of the Red Cross to a a country at war under International Law and how a violation of Geneva Convention IV of 1949 by countries at war. Authors conducted a study in this thesis is Library Research, by collecting data sourced from literature. Sources contained in this literature study is books, journals, articles, dictionary, newspaper, electronic data, also primary data as well as conventions that are used as reading in this paper. Normative Legal research that examines the ways reading, analyzing, interpreting, comparing and also translated various sources that where these resources associated with this paper. Geneva Convention IV provides the protection of civilians in time of war. This convention composed entirely 159 chapters and three attachments. Several groups of civilians to be protected is foreigners in occupied or which are also referred to citizens in the territory of the enemy civil disputants, then people who live in the occupied territories which is also called the civilian population in the occupied territories and also civilian internees in which civilians may be interned protected. International Committee if the Red Cross have a role to countries at war by providing humanitarian aid. There are some violations of the provisions of articles contained in the Geneva Conventions IV of 1949 by countries at war. [1] Mahasiswa Fakultas Hukum Universitas Sumatera Utara [2] Dosen Fakultas Hukum Universitas Sumatera Utara [3] Dosen Fakultas Hukum Universitas Sumatera Utara